Perceptions on Hearing Aid Use and Its Influence on Self-Esteem of Learners With Hearing Impairment in Integrated Settings in Nairobi City County, Kenya - Thiga, Elizabeth M.; Awori, Beatrice Bunyasi; Abuom, Tom (Journal of Education and Training, 2023)
Hearing impairment has been linked to low self-esteem in children. Many teachers have noted that a growing number of students are unwilling to wear hearing aids, even though non-governmental groups such as the Starkey Ear Foundation provide them free of charge. The study aimed to discover how learners with hearing impairment in integrated units in Nairobi City County, Kenya, felt about hearing aid use and how it affected their self-esteem. Peter Burke's Identity Control Theory directed the research. The study was conducted using a descriptive survey design. Headteachers, teachers in charge of learners with hearing impairment, parents, and learners with and without hearing impairment were the target population. A total of 90 participants were surveyed, including 8 headteachers, 15 parents, 8 teachers, 51 learners with hearing impairment who used hearing aids, and 8 learners who did not have hearing problems. Data was gathered by the distribution of questionnaires to learners, parents, and instructors, as well as a complementing interview with the headteachers. Pilot research was undertaken in a Nairobi primary school. Descriptive statistics were used to analyze the quantitative data. The computer programme SPSS version 22.0 was used to do inferential statistics. Thematic analysis was done on qualitative data. The study discovered that learners with hearing loss had generally positive attitudes concerning hearing aid use. Hearing aid use had a weak positive influence on the self-esteem of learners with hearing impairment as per the study's overall findings. The study recommends that the government provide schools with speech therapists/audiologists to follow up on language intervention of learners with hearing impairment who are wearing hearing aids, as well as encourage collaboration of a multi-disciplinary team that includes teachers, parents, headteachers, audiologists/speech therapists to ensure that they benefit from hearing aid use and improve their self-esteem.